Administración de antibióticos por vía parenteral y su relación con los efectos adversos en gestantes adolescentes que acuden al centro de salud Zapotal nuevo, ventanas, los Ríos, segundo semestre 2017. - ALBUJA CHALA, JOHANNA YADIRA (2018)
In the following, descriptive / exploratory research was used, 16 million girls between the ages of 15 and 19, and approximately 1 million girls under the age of 15 give birth each year, mostly in low- and middle-income countries. Complications during pregnancy and childbirth are the second leading cause of death among adolescents worldwide. Each year, some 3 million girls aged 15 to 19 years undergo dangerous abortions. The physiological changes that occur during pregnancy can modify the pharmacokinetics of drugs in the different phases of the same (absorption, distribution, metabolism, elimination) and these changes can affect their safety and effectiveness. The methodology of the research to be developed is the non-experimental and field research as support in the development of research that aims to identify what are the adverse effects that occur in the administration of antibiotics in pregnant women, demonstrating each of the causes of the problem. Therefore it has been established that the conclusion was developed by means of the age of greatest incidence in adolescent pregnant women is from 15 to 17 years in the Zapotal Nuevo Health Center, Second Semester 2017; The trimester of gestation with the highest risk of adverse effects is the first trimester since antibiotics pass the placental barrage. Babies born to teenage mothers face a significantly higher risk of dying than those born to women aged 20 to 24 years. 100% of adolescent pregnant women were given antibiotics due to the discomfort caused by infections.